타액선 다형성선종 환자의 임상적 연구 - 김종렬(Jong-Ryoul Kim); 박봉욱(Bong-Wook Park); 변준호(June-Ho Byun); 김용덕(Yong-Deok Kim); 신상훈(Sang-Hoon Shin); 김욱규(Uk-Kyu Kim); 정인교(In-Kyo Chung) (Journal of the Korean Association of Oral and Maxillofacial Surgeons, 2005)
KCI Citation Count: 1